Physicochemical processing of polyphenylsulfone: Optimization of processing parameters for microsphere production via spray drying using a response surface model. Issue 8 (2nd January 2019) - Mys, Nicolas; Geiregat, Maarten; Deruyck, Frank; Verberckmoes, An; Cardon, Ludwig
Abstract: This article describes the processing of polyphenylsulfone (PPSU) into microspheres via the physicochemical method called spray drying (SD). Polymeric microspheres have a potential in various fields of research like diagnostics, separations, thermal insulations, pigments, and additive manufacturing like selective laser sintering (SLS). These microspheres have the potential to be used as building material for SLS provided they have spherical morphology and have a submicrometer particle size. The effects of the different processing parameters on these two response factors have been investigated in SD of PPSU by design of experiment. A plot is predicted in which size and morphology are optimized and combined in order to find the ideal parameter set for production. The effect of polymer concentration, solution feed rate, atomization flow rate, inlet temperature, and polymer grade was optimized using a five‐factor three‐level factorial design. Through the statistical model, particles with a mean particle size of 13.27 μm can be obtained of which 19% are of adequate sphericity and roundness according to Powers' scale for the low viscous grade (R5600, Radel® R5600 Solvay polymer, low viscous grade (or very high melt flow grade) of PPSU). In the case of the high viscous grade (R5000, Radel ® R5000 Solvay polymer, high viscous grade of PPSU), a best particle size of 12.48 μm with 12.5% spherical particles can be achieved.